Innovative Approaches in Islamic Education: Imre Lakatos' Methodological Paradigm and Its Implications - Mandar, Yasri; Putri, Musdalipah; Lutan Hidayah, Ahwil; Hidayat, Yusron; Nida, Sofwatun (Program Studi Pendidikan Agama Islam Fakultas Tarbiyah dan Keguruan UIN Sultan Maulana Hasanuddin Banten, 2025)
Along with the development of the times, human knowledge is increasingly developing so that branches of Islamic education science are born. The progress of the times is also inseparable from the birth of new complex problems, especially in Islamic education. this requires multidisciplinary science to be able to formulate innovative solutions with the Imre Lakatos paradigm and its implications in Islamic education. This research uses qualitative methods (library research). The data used is from Primary and secondary sources generated from several literatures and the presentation of data presented in the form of descriptive . Then, this research aims to explain the paradigm of Imre Lakatos' thinking methodology. In the research program methodology Imre Lakatos says that knowledge is sustainable and the core of his thinking is hard core, protectives-belt, and a series of theory. Lakatos' research program uses the heoristic method. Its relevance to Islamic education lies in the Qur'an and Sunnah which are the core of Islamic understanding serving as the main pillars on which Islamic studies are built. Both are known as protective belts because they have absolute quality and can be understood in various scientific contexts.